Response of diatom assemblages to the disruption of the running water continuum in urban areas, and its consequences on bioassessment - Ewelina Szczepocka (PeerJ Inc., 2021)
Transformation of river and stream channels disrupts their natural ecological cycles and interrupts the continuum of their ecosystems. Changes in natural hydromorphological conditions transform lotic communities into those atypical of flowing waters, resulting in bioassessment procedures yielding incorrect results. This study shows how hydromorphological transformations of ecosystems affect the ecological status bioassessment results by disturbing diatom communities typical for rivers. Moreover, the article presents a new biological assessment procedure for urban transformed rivers including the verification of the community structure based on autecology and quantity of species. The ecological status of the ecosystem was assessed using benthic diatom assemblages and supported with results of hydrochemical analysis. The structure of the assemblages and their relationships between individual sampling sites were clarified by shade plot and multivariate data analyses. The analysis of dominant species vitality at sampling sites and their autecology gave the foundation for modification of taxa data matrix and recalculation the diatom indices. Biological assessment showed that one of the artificial ponds constructed at the stream channel was characterized by good ecological status, and its presence strongly affected the state of the downstream ecosystem following the development of a unique assemblage of diatoms that prefer oligosaprobic and oligotrophic waters. The presence of these species was also noted in the downstream sections, but most of the cells were dead. As the indicator values of these taxa are high, their presence artificially increased the ecological status of the stream, resulting in the hydrochemical assessment not being in line with the bioassessment. Therefore, a new procedure was adopted in which non-characteristic taxa for the downstream sections were excluded from analysis. This approach corrected the results of bioassessment characterizing the ecological status of the stream as poor along its entire course, with the exception of this unique pond. For hydromorphologically transformed streams and rivers with disturbed channel continuity, the correct result of an incorrect diatom-based bioassessment may be retrieved after excluding species unusual for the type of ecosystem from the studied assemblages, i.e., the species which are unable to reproduce in that area and are only carried into it by the water flow. Assessment of the ecological status of aquatic ecosystems based on biotic factors is an essential tool of aquatic ecosystems monitoring in many countries. This type of assessment requires a multifaceted approach, in particular, to identify factors that may disrupt this assessment. Standardization of biomonitoring methods is an important step in correct assessment; thus, the findings of this paper will be useful in routine biomonitoring around the world.